Two patients with Kabuki syndrome presenting with endocrine problems - BEREKET, ABDULLAH; ALPAY, HARİKA (My University, 2001)
A 4 year-old boy with mental retardation and seizures presented to the pediatric endocrinology clinic because of a history of hypoglycemia; a 16 month-old girl with developmental delay presented with bilateral breast tissue enlargement; in both, a diagnosis of Kabuki syndrome was made because of typical facial features, neurodevelopmental delay and other stigmata consistent with Kabuki syndrome. Kabuki syndrome is a mental retardation-malformation syndrome affecting multiple organ systems with a broad spectrum of abnormalities. The facial features of the syndrome are specific and independent of ethnic origin. In addition to presenting with endocrine problems, the patients reported here exhibit some novel findings such as congenital alopecia areata and hyperpigmented skin lesion. The diagnosis of Kabuki syndrome should be considered in patients with hypoglycemia or premature thelarche when associated with developmental delay and a peculiar facies.
Keywords: Female; Humans; Syndrome; Infant; Male; Child, Preschool; Facies; Developmental Disabilities; Intellectual Disability; Seizures; Endocrine System Diseases